Functional inhibition of core spliceosomal machinery activates intronic premature cleavage and polyadenylation of pre-mRNAs - Qiumin Feng; Zejin Lin; Danhui Zhao; Mengzhao Li; Sheng Yang; Andy Peng Xiang; Congting Ye; Chengguo Yao (Cell Reports, 2025)
Summary: The catalytic role of U6 snRNP in pre-mRNA splicing has been well established. In this study, we utilize an antisense morpholino oligonucleotide (AMO) specifically targeting catalytic sites of U6 snRNA to achieve functional knockdown of U6 snRNP in HeLa cells. The data show a significant increase in global intronic premature cleavage and polyadenylation (PCPA) events, similar to those observed with U1 AMO treatment, as demonstrated by mRNA 3′-seq analysis. Mechanistically, we provide evidence that U6 AMO-mediated splicing inhibition might be the driving force for PCPA as application of another specific AMO targeting U2 snRNP results in similar global PCPA effects. Together with our recently published findings that demonstrate the global inhibitory effect of U4 snRNP on intronic PCPA, our data highlight the critical role of splicing in suppressing intronic PCPA and support a model in which splicing and polyadenylation may compete with each other within introns during co-transcriptional mRNA processing.